Educare al poetico? (Materiali di Estetica. Terza serie, 2020)
The relationship between education and poetry, concerning a personal and intimate aspect through the reader and the text, is perhaps the most difficult to grasp and to depict. For this reason, it would be more suitable to refer it, on the one hand, to ‘self-formation’ and, on the other hand, to the ‘ineffable’ of poetics. It deals with two paradigms of cultural life that need sensitivity and attention, caring and listening. Although they don’t seem to match with the present time (the time of usefulness, of performativity, of aloofness), the self-formation and the experience of ineffable are two dimensions that explicitly go through and characterise current youth. In many ways. Then, the Educator has the task to show the path that, through Arts, leads everyone to him/herself.
Keywords: Formation of self; Poetics; Ineffable